Enhanced moisture repulsion of ceramic-coated separators from aqueous composite coating solution for lithium-ion batteries inspired by a plant leaf surface. Issue 14 (3rd March 2016) - Kim, Sang Woo; Cho, Kuk Young
Abstract : In this study, we demonstrate enhanced moisture repulsion of aqueous processed ceramic coated separators inspired by the distributed wax domain on a plant leaf surface. Abstract : Biomimetic approaches in the preparation of components for lithium-ion batteries can provide new solutions to current challenging issues. We demonstrate the facile fabrication of a ceramic-coated separator (CCS) that exhibits enhanced moisture repulsion despite the use of an aqueous coating solution in the preparation. The hydrophobic character of the surface increased with the amount of micron-scale wax domain on the surface without deteriorating the charge and discharge cycle performance of the cell equipped with new CCSs.